THE SCIENCE OF ACHIEVEMENT AND MOTIVATION - Rustamova, Adash Eshankulovna; Bakhriddinova, Farangiz Bobir qizi (INTERNATIONAL CONFERENCES, 2023)
In this article, you will be informed about not only how you can reach successful performance on your work or studies but also some top achievement motivation. Hope, it can be useful instruction in your life.